From Goethe to Gundolf Essays on German Literature and Culture - Paulin, Roger (Open Book Publishers, 2021)
"From Goethe to Gundolf: Essays on German Literature and Culture is a collection of Roger Paulin's groundbreaking essays, spanning the last forty years. The work represents his major research interests of Romanticism and the reception of Shakespeare in Germany, but also explores a broader range of themes, from poetry and the public memorialization of poets to fairy stories - all meticulously researched, yet highly accessible. As a comprehensive examination of German literary history in the period 1700-1900, the collection not only includes accounts of the lives and work of Goethe, Schiller, the Schlegels, and Gundolf (amongst others), serving to nuance our understanding of these figures in history, but also considers diverse (and often underexplored) topics, from academic freedom to the rise of travel literature. The essays have been reformulated, corrected, and updated to add references to recent works. However, the core foundations of the originals remain, and just as when they were first published, the value of these essays - to researchers, students, and all those who are interested in German literary history - cannot be overstated."